PENDAMPINGAN MAHASISWA PROGRAM KAMPUS MENGAJAR DALAM RANGKA PENGUATAN LITERASI, NUMERASI, DAN ADAPTASI TEKNOLOGI DI SMK NEGERI 2 KAYUAGUNG - Firmansyah, Firmansyah; Ali, Mukti; Prasada, Erisa Ardika (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
This community service activity is intended to: 1) improve students' ability to provide classroom assistance, 2) improve students' ability to develop students' literacy and numeracy, and 3) improve students' ability to adapt technology to students' learning and academic activities. The mentoring method is carried out through 4 stages, namely: 1) planning stage, 2) implementation stage, 3) evaluation and monitoring, and 4) reporting. The results of this mentoring activity have significantly improved students' abilities in: 1) providing classroom assistance, 2) developing student literacy and numeracy, and 3) adapting technology to student learning and academic activities. These indicators can be seen from the various activities that have been carried out by students in an effort to strengthen literacy, numeracy, and technology adaptation at SMK Negeri 2 Kayuagung.